Calibration of indoor temperature and relative humidity readings in the PurpleAir monitor - Kyle T. Aune; Megan Wilks; Timothy Green; Ana M. Rule; Meredith McCormack; Nadia N. Hansel; Nirupama Putcha; Gregory Kirk; Sarath Raju; Kirsten Koehler (Environmental Monitoring and Assessment, 2025)

Indoor particulate matter concentrations and air cleaner intervention association with biomarkers in former smokers with COPD - Ashraf Fawzy; Han Woo; Sarath Raju; Daniel C. Belz; Nirupama Putcha; Marlene S. Williams; Meredith C. McCormack; Kirsten Kohler; Nadia N. Hansel (Environmental Research, 2024)

Associations between mitochondrial biomarkers, urban residential exposures and childhood asthma outcomes over 6 months - Rachel L. Miller; Janelle Rivera; Lydia Lichtiger; Usha S. Govindarajulu; Kyung Hwa Jung; Stephanie Lovinsky-Desir; Frederica Perera; Susan Balcer Whaley; Michelle Newman; Torie L. Grant; Meredith McCormack; Matthew Perzanowski; et al. (Environmental Research, 2023)

Evaluation of calibration approaches for indoor deployments of PurpleAir monitors - Kirsten Koehler; Megan Wilks; Timothy Green; Ana M. Rule; Misti L. Zamora; Colby Buehler; Abhirup Datta; Drew R. Gentner; Nirupama Putcha; Nadia N. Hansel; Gregory D. Kirk; Sarath Raju; et al. (Atmospheric Environment, 2023)

UISCEmod: Open-source software for modelling water level time series in ephemeral karstic wetlands - Joan Campanyà; Ted McCormack; Laurence William Gill; Paul Meredith Johnston; Andrea Licciardi; Owen Naughton (Environmental Modelling & Software, 2023)

A cross sectional pilot study to assess the role of phthalates on respiratory morbidity among patients with chronic obstructive pulmonary disease - Lesliam Quirós-Alcalá; Daniel C. Belz; Han Woo; Wendy Lorizio; Nirupama Putcha; Kirsten Koehler; Meredith C. McCormack; Nadia N. Hansel (Environmental Research, 2023)

Principal stratification analysis to determine health benefit of indoor air pollution reduction in a randomized environmental intervention in COPD: Results from the CLEAN AIR study - Han Woo; Kirsten Koehler; Nirupama Putcha; Wendy Lorizio; Meredith McCormack; Roger Peng; Nadia N. Hansel (Science of The Total Environment, 2023)

Landscape genetics of California mule deer ( Odocoileus hemionus ): the roles of ecological and historical factors in generating differentiation - KATHERINE M. PEASE; ADAM H. FREEDMAN; JOHN P. POLLINGER; JOHN E. MCCORMACK; WOLFGANG BUERMANN; JEFF RODZEN; JIM BANKS; ERIN MEREDITH; VERNON C. BLEICH; ROBERT J. SCHAEFER; KEN JONES; ROBERT K. WAYNE (Molecular Ecology, 2009)
Landscape genetics is an emerging discipline that utilizes environmental and historical data to understand geographic patterns of genetic diversity. Niche modelling has added a new dimension to such efforts by allowing species–environmental associations to be projected into the past so that hypotheses about historical vicariance can be generated and tested independently with genetic data. However, previous approaches have primarily utilized DNA sequence data to test inferences about historical isolation and may have missed very recent episodes of environmentally mediated divergence. We type 15 microsatellite loci in California mule deer and identify five genetic groupings through a Structure analysis that are also well predicted by environmental data. We project the niches of these five deer ecotypes to the last glacial maximum (LGM) and show they overlap to a much greater extent than today, suggesting that vicariance associated with the LGM cannot explain the present‐day genetic patterns. Further, we analyse mitochondrial DNA (mtDNA) sequence trees to search for evidence of historical vicariance and find only two well‐supported clades. A coalescence‐based analysis of mtDNA data shows that the genetic divergence of the mule deer genetic clusters in California is recent and appears to be mediated by ecological factors. The importance of environmental factors in explaining the genetic diversity of California mule deer is unexpected given that they are highly mobile species and have a broad habitat distribution. Geographic differences in the timing of reproduction and peak vegetation as well as habitat choice reflecting natal origin may explain the persistence of genetic subdivision.